Video clips on Rift Valley fever customised for dissemination using smart phones - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The RVF video clips were developed and disseminated to farmers, traders and veterinary professionals in June 2018. This coincided with the RVF outbreak that occurred in Kenya. Sidai Africa, an NGO that works in the region also requested copies for use in their trainings.